The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1093/annonc/mdq333
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 mRNA expression and outcome to neoadjuvant cisplatin-based chemotherapy in bladder cancer

Abstract: Background: Neoadjuvant chemotherapy has shown a modest benefit in muscle-invasive bladder cancer patients; however, the subset of patients most likely to benefit has not been identified. BRCA1 plays a central role in DNA repair pathways and low BRCA1 expression has been associated with sensitivity to cisplatin and longer survival in lung and ovarian cancer patients. Patients and methods:We assessed BRCA1 messenger RNA expression levels in paraffin-embedded pre-treatment tumor samples obtained by transurethral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 33 publications
0
60
0
2
Order By: Relevance
“…Takata et al reported that 14 genes were found to be predictive of pCR and may be prognostic factors in patients with bladder cancer treated with neoadjuvant M-VAC therapy (10,26). With regard to DNA repair genes, BRCA1 mRNA was reported to predict the efficacy of cisplatin-based NC (8). In the present study, although the co-expression of Snail and ERCC1 was not a significant factor for the prediction of CR to NC, notably, the co-expression of the proteins, and not just the individual expression of ERCC1 or Snail, was identified as significant prognostic factors for shorter DFS and OS in the patients treated with a cisplatin-based regimen and also those treated with the M-VAC regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takata et al reported that 14 genes were found to be predictive of pCR and may be prognostic factors in patients with bladder cancer treated with neoadjuvant M-VAC therapy (10,26). With regard to DNA repair genes, BRCA1 mRNA was reported to predict the efficacy of cisplatin-based NC (8). In the present study, although the co-expression of Snail and ERCC1 was not a significant factor for the prediction of CR to NC, notably, the co-expression of the proteins, and not just the individual expression of ERCC1 or Snail, was identified as significant prognostic factors for shorter DFS and OS in the patients treated with a cisplatin-based regimen and also those treated with the M-VAC regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy (NC) with cisplatin-based combination chemotherapy significantly improved the 5-year survival rate in two meta-analysis studies (4,5) and pathological complete response (pCR) with NC was correlated with survival (6,7). Although a number of studies have discussed factors which predict pCR or a favorable survival rate (8)(9)(10), none of the factors has been proven in a clinical study.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of clinical studies have examined the utilization of this BRCA1 dysfunction in response to the DNA-damaging drug cisplatin. A pathological complete response (pCR) with excellent compliance was observed in cancer patients with BRCA1 mutations (Byrski et al, 2009;Font et al, 2010;Quinn et al, 2007;Silver et al, 2010;Taron et al, 2004). This indicates that patients with BRCA1 dysfunction gain more benefit from treatments that exert their effects by causing DNA damage.…”
Section: Cisplatin-protein Adductsmentioning
confidence: 99%
“…Ein weiterer prognostischer Marker ist das BRCA1 ("breast cancer 1"), welches ebenfalls eine Rolle für die Reparatur von DNA-Schäden durch Cisplatin spielt. Bei Patienten, die mit eine neoadjuvanten Chemotherapie behandelt worden sind, zeigt sich ebenfalls ein statistisch signifikanter Überlebensvorteil, wenn eine niedrige BRCA1-Expression vorliegt [20]. Die mRNA-Expression von Survivin und Emmprin konnte in einer Microarray-basierten Analyse ebenfalls als unabhängige Prognosemarker für das Überleben von Patienten nach Cisplatin-basierter Chemotherapie identifiziert werden [21].…”
Section: Perioperative Therapie Des Lokal Fortgeschrittenen Harnblaseunclassified